CURRENT STATE OF WINTER RYE SEED PRODUCTION IN UKRAINE - Biliavska, L. H.; Biliavskyi, Yu. V. (Scientific Progress & Innovations, 2021)
The article presents the results of analyzing the current state of winter rye sowing material production (Secale cereale L.). The largest ten producers of winter rye seeds in the world are Germany, Russia, Poland, Belarus, Denmark, China, Ukraine, Turkey, Spain and Austria. The average yield of winter rye in the countries for the period of 2017–2019 is given. Thus, in Ukraine, the area under rye made 740 thousand hectares in 2004 and 150 thousand hectares in 2018. The dynamic renewal of variety assortment has been taking place for the recent 12 years. The State Register of Plant Varieties Suitable for Distribution in Ukraine contained 40 winter rye varieties, of which 21 varieties of Ukrainian selection and 19 varieties of foreign selection in 2019 and 56 varieties and hybrids in 2021. There is the obvious tendency of increasing varieties of foreign selection from 6 % to 47 %. At the same time, the competitiveness of varieties of Ukrainian selection prevails. The leaders in the cultivation of winter rye in Ukraine are Zhytomyr, Volyn, Chernihiv, Rivne, Kyiv, Sumy, Khmelnytskyi and other regions. The most important conditions for increasing the crop yields are large-scale introduction of the best varieties into production and the improvement of seed quality in the amounts required for the regions. Genetic and biological and economically valuable traits of the variety, soil and climatic conditions of cultivation and other factors are taken into account in the production of high-quality rye seeds. Seed production of winter rye envisages the concentration of production processes on the certified seed growing farms, the number of which in Ukraine is gradually reducing. These farms produce certified seeds in order to satisfy the full requirements of agricultural producers of commercial grain. The certification model, equal conditions and opportunities for all producing companies (national and foreign) were created for seed producers in our country, which guarantees them the status a commercial product manufacturer. The analysis of the variety assortment of winter rye seed areas showed the predominance of Ukrainian selection varieties – more than 80%, but their share is steadily decreasing. The use of reproductive seeds on seed growing farms contributes to the product deterioration obtained under the influence of biological and mechanical contamination, damage by diseases, pests and a low level of agricultural technology. Well-organized seed production can slow this process down, but it can be difficult to stop.